Clinical-Grade Isolated Human Kidney Perivascular Stromal Cells as an Organotypic Cell Source for Kidney Regenerative Medicine. (20th September 2016) - Leuning, Daniëlle G.; Reinders, Marlies E.J.; Li, Joan; Peired, Anna J.; Lievers, Ellen; de Boer, Hetty C.; Fibbe, Willem E.; Romagnani, Paola; van Kooten, Cees; Little, Melissa H.; Engelse, Marten A.; Rabelink, Ton J.
Abstract: Mesenchymal stromal cells (MSCs) are immunomodulatory and tissue homeostatic cells that have shown beneficial effects in kidney diseases and transplantation. Perivascular stromal cells (PSCs) identified within several different organs share characteristics of bone marrow-derived MSCs (BM-MSCs). These PSCs may also possess tissue-specific properties and play a role in local tissue homeostasis. We hypothesized that human kidney-derived PSCs (hkPSCs) would elicit improved kidney repair in comparison with BM-MSCs. Here we introduce a novel, clinical-grade isolation method of hkPSCs from cadaveric kidneys by enriching for the perivascular marker, NG2. hkPSCs show strong transcriptional similarities to BM-MSCs but also show organotypic expression signatures, including the HoxD10 and HoxD11 nephrogenic transcription factors. Comparable to BM-MSCs, hkPSCs showed immunosuppressive potential and, when cocultured with endothelial cells, vascular plexus formation was supported, which was specifically in the hkPSCs accompanied by an increased NG2 expression. hkPSCs did not undergo myofibroblast transformation after exposure to transforming growth factor-β, further corroborating their potential regulatory role in tissue homeostasis. This was further supported by the observation that hkPSCs induced accelerated repair in a tubular epithelial wound scratch assay, which was mediated through hepatocyte growth factor release. In vivo, in a neonatal kidney injection model, hkPSCs reintegrated and survived in the interstitial compartment, whereas BM-MSCs did not show this potential. Moreover, hkPSCs gave protection against the development of acute kidney injury in vivo in a model of rhabdomyolysis-mediated nephrotoxicity. Overall, this suggests a superior therapeutic potential for the use of hkPSCs and their secretome in the treatment of kidney diseases.